Introduction to the special collection in memoriam of Susan A. Odom (16 November 1980–18 April 2021). Issue 20 (15th September 2022) - Augustyn, Veronica; Hatzell, Kelsey B.; Jeffries-EL, Malika; Lutkenhaus, Jodie L.; Stingelin, Natalie
Abstract : The materials chemistry and electrochemistry communities celebrate Susan's scientific impact and collaborative spirit with this themed issue.